Pengembangan Media Buku Panduan Aktivitas Dalam Pencegahan Perundungan (Bullying) - Renti; Nita Priyanti; Hamid Patilima (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2026)
Bullying in early childhood is a social and emotional problem that may hinder children's development if not addressed at an early stage. A needs analysis conducted at TP PAUD Melati 8, Sukabumi Regency, revealed that teachers lacked a specific instructional medium to systematically implement bullying prevention activities. This study aimed to develop the “Aku Teman Baik” Activity Guidebook as a learning medium to support bullying prevention among young children. The research employed a Research and Development (R&D) method using the ADDIE model. The participants were children aged 5–6 years at TP PAUD Melati 8, Sukabumi Regency. Data were collected through questionnaires, interviews, observation, and documentation. The results indicated that the teachers’ need for the media reached 91.4%, while the children’s need reached 88.4%. Product validation showed a very high feasibility level, with material experts scoring 91.2%, media experts 91.2%, and child development experts 95.8%. The effectiveness of the product was demonstrated by an increase in the average score from 52% in the pretest to 81% in the posttest, representing a 57% improvement categorized as very effective. These findings indicate that the “Aku Teman Baik” Activity Guidebook is feasible and effective for supporting bullying pevention in early childhood education.